Hubungan Coping Stress Dengan Prokrastinasi Pada Mahasiswa Semester Akhir - Naomi Paat; Ellen Yorensa; Irene Fanri Putri; Jessica Chandhika (Departement of Mathematics Education, 2023)
As a college students, it will be a difficult thing to avoid stress. College students certainly have different ways to dealing with their stress. Of course, many of them overcome their stress with positive things, but unfortunately many of them also overcome their stress with procrastination. Procrastination itself is a common thing that happens to many people, especially college students, especially when they are in final semester and working at the same time. Assignments that come from college and work at the same time make stress and pressure even higher, thus allowing higher procrastination to occur so they can avoid stress. Through this statement, the researchers tries to find out whether there is a significant relationship between coping stress and procrastination in a final semester college students who also working. In this research, researchers are using correlational quantitative method. The research subjects consisted of 90 final semester college students who also currently working.